Lemierre Syndrome with Extensive Thrombosis: A Unique Case Report and Literature Review - Stergos Koukias; Asimenia Athousaki; Dionisios Klonaris; Melina Kavousanaki; Georgios Papazoglou; Nikolaos Papanikolaou (Case Reports in Otolaryngology)
Background. Lemierre syndrome (LS) is a rare complication of upper aerodigestive tract infections characterized by proximal and distal septic emboli, commonly including internal jugular vein (IJV) thrombosis. Diagnosis can be challenging, and treatment delays can result in increased patient morbidity and mortality. We present a rare case of LS with extensive thrombosis and multiple sites of distal infection and a narrative review of the literature. Case Presentation. A 52-year-old Caucasian male was transferred to the emergency department (ED) with an altered level of consciousness and clinical findings of acute bacterial pharyngotonsillitis. Medical history included cervical spine disorder and traumatic brain injury in the past, as well as the recent use of pain relievers due to acute cervical pain. Imaging studies revealed left IJV thrombosis that extended into multiple venous cerebral sinuses and infiltrates of the right lung. LS was considered the most likely diagnosis. The patient was intubated and transferred to the intensive care unit (ICU). Treatment included intravenous broad-spectrum antibiotics and anticoagulation therapy. Response to treatment was satisfactory. After extubation, he was transferred to a ward and discharged with resolution of clinical and imaging findings. Conclusion. LS is a rare disease and may have an insidious course. Timely diagnosis and appropriate treatment strategies, mainly broad-spectrum antibiotics, offer favorable outcomes in otherwise healthy individuals. The indications for anticoagulation therapy still remain controversial. Anticoagulants are usually administered to patients with extensive thrombosis. Surgical treatment includes abscess drainage, while IJV ligation and excision are reserved for nonresponders to medical treatment.